Effect of bedding mortar with low strength and high entrained air content on the strain and failure mode of masonry prisms under compression - Isabela Naia Talhacoli; André Lübeck; Gihad Mohamad (REM: International Engineering Journal, 2025)
Abstract Brazilian standards regarding structural masonry does not consider the effect of bedding mortar properties on the strength and failure mode of masonry. Thus, the objective of this study was to evaluate the effect of bedding mortars with low strength and high entrained air content on the stress-strain curve and failure mode of masonry prisms under compression. The prisms were constructed from concrete or ceramic blocks (hollow core or solid) and mortars with low strength and high entrained air content. Three types of mortars were tested, one dry pre-mixed mortar and two ready-to-use, with open times of 36 and 72 h. All physical and mechanical properties of the materials were determined following Brazilian standards. Strain under compression was evaluated on two-block high prisms equipped with linear variable differential transformers (LVDT) placed on opposing faces. Results pointed out that both strength and strain of ceramic block prisms were affected by mortar strength. On the other hand, the concrete block prism strength was affected by mortar strength and porosity while strain was largely affected by mortar porosity. Failure modes differed between ceramic and concrete block prisms: ceramic prisms cracked from mortar joint crushing and resulted in structural failure, while concrete prisms lost block-mortar adhesiveness from joint crushing. Therefore the prism was no longer a single entity but was still able to withstand the axial compression stress test.